2012
DOI: 10.1186/2047-783x-17-21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an acetate- and a lactate-based balanced infusion solution on acid base physiology and hemodynamics: an observational pilot study

Abstract: BackgroundThe current pilot study compares the impact of an intravenous infusion of Ringer’s lactate to an acetate-based solution with regard to acid–base balance. The study design included the variables of the Stewart approach and focused on the effective strong ion difference. Because adverse hemodynamic effects have been reported when using acetate buffered solutions in hemodialysis, hemodynamics were also evaluated.MethodsTwenty-four women who had undergone abdominal gynecologic surgery and who had receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…The hemodynamics profile remained stable throughout and was comparable in both groups. Although acetatecontaining solutions have been reported to cause severe hemodynamic instability due to increased nitric oxide synthesis and enhanced arrhythmias, this was only noted in patients who were undergoing haemodialysis [14]. In our study, we did not infuse any glucose solution intravenously.…”
Section: Discussionmentioning
confidence: 90%
“…The hemodynamics profile remained stable throughout and was comparable in both groups. Although acetatecontaining solutions have been reported to cause severe hemodynamic instability due to increased nitric oxide synthesis and enhanced arrhythmias, this was only noted in patients who were undergoing haemodialysis [14]. In our study, we did not infuse any glucose solution intravenously.…”
Section: Discussionmentioning
confidence: 90%
“…The balanced solution gives a more stable plasma bicarbonate level. A pilot study by Hofmann-Kiefer showed that slight advantages were observed in the acetate-buffered solution in terms of pH and plasma HCO3-stability in comparison with the lactate-based balanced solution (25). The balanced solution with acetate buffer is also more advantageous than a lactate-based buffer in terms of metabolism and clearance because it does not depend on the liver function (14).…”
Section: Discussionmentioning
confidence: 99%
“…In a small study comparing the use of balanced solutions containing either lactate (Lactated Ringer's) or acetate for patients undergoing abdominal gynecologic surgery, both solutions showed similar effects on hemodynamic stability and vasopressor use. However, acetate-based solution led to a greater stability of the plasma SID, with a decrease in pH and serum bicarbonate concentrations in the group that received Lactated Ringer's [16].…”
Section: Key Pointsmentioning
confidence: 91%